PENYELESAIAN PERSELISIHAN HUKUM INDUSTRIAL ANTARA PT. INDOSURYA SIMPAN PINJAM CABANG PEKANBARU DENGAN KARYAWAN BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2004 TENTANG PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - KENNISA MAHARANI; Hayatul Ismi; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Termination of employment is regulated in Articles 150 to Article 170 ofLaw Number 13 of 2003 concerning Employment, Process for resolving disputesbetween mediators from the Riau Province Manpower and TransmigrationService. , conciliation, arbitration and settlement in the Industrial RelationsCourt. The settlement of the mediation is not reached peace, because the result ofthe mediation. The main problem is how to implement termination of employmentat the mediation level in the context of resolving industrial relations disputes atthe Manpower and Transmigration Office of Riau Province and what are theobstacles in resolving disputes over termination of employment at the mediationlevel in the context of resolving industrial relations disputes according to the Law.The study took a sample from a population and used interviews as a meansof collecting basic data. The nature of descriptive research is to describe thecurrent state of the subject or object of research based on the facts that appear asthey are. Implementation of the settlement of disputes over termination ofemployment (PHK) at the mediation level at the Office of Manpower andTransmigration of Riau Province, namely the mediator acts as a neutral andarbiter of parties, helping to solve problems and finding solutions to the disputesencountered. mediation and mediation stage, at the pre-mediation stage themediator collects background information and facts of the dispute, at themediation stage, the mediator carries out mediation according to his capacity tobe able to produce the right solution so that termination of employment can beavoided and is impartial and neutral in resolving disputes.Barriers to the Implementation of Dispute Settlement Termination at themediation level at the Manpower and Transmigration Service, namely: it isdifficult to find the presence of the leadership of PT.Indosurya Pekanbaru branchor central, due to the reason the leadership is not always in the office when youwant to be met, the distance traveled by the parties because the location of themediation place is far from their place of origin, the handling is not completed bythe mediator, there is no agreement with proof of signing the agreement file. Theexistence of different points of view, reluctance to understand what is conveyed bythe mediator, does not accept the opinion of the mediator.Keywords: Settlement-Industrial Law Disputes-Employees